An in vitro Reconstructed Human Skin Equivalent Model to Study the Role of Skin Integration Around Percutaneous Devices Against Bacterial Infection - Bolle, Eleonore C. L.; Verderosa, Anthony D.; Dhouib, Rabeb; Parker, Tony J.; Fraser, John F.; Dargaville, Tim R.; Totsika, Makrina (Frontiers in Microbiology, 2020)
Percutaneous devices are a key technology in clinical practice, used to connect internal organs to external medical devices. Examples include prosthesis, catheters and electrical drivelines. Percutaneous devices breach the skin’s natural barrier and create an entry point for pathogens, making device infections a widespread problem. Modification of the percutaneous implant surface to increase skin integration with the aim to reduce subsequent infection is attracting a great deal of attention. While novel surfaces have been tested in various in vitro models used to study skin integration around percutaneous devices, no skin model has been reported, for the study of bacterial infection around percutaneous devices. Here, we report the establishment of an in vitro human skin equivalent model for driveline infections caused by Staphylococcus aureus, the most common cause of driveline-related infections. Three types of mock drivelines manufactured using melt electrowriting were implanted in human skin constructs (smooth or porous un-seeded and porous pre-seeded with human fibroblasts) and challenged with S. aureus. Our results show a high and stable load of S. aureus in association with the skin surface and no signs of S. aureus-induced tissue damage. Furthermore, our results demonstrate that bacterial migration along the driveline surface occurs in micro-gaps caused by insufficient skin integration between the driveline and the surrounding skin consistent with clinical reports from explanted patient drivelines. Thus, the human skin-driveline infection model presented here provides a clinically-relevant and versatile experimental platform for testing novel device surfaces and infection therapeutics.